Tree rings of Quercus ilex L. and their relationships with some wood anatomical features and growing site conditions in Türkiye - SEVGİ, ECE; AKKEMİK Ü.; YILMAZ H.; SEVGİ O.; ÇELİK ONAR H.; YILMAZ O. Y.; SEVGİ E.; Genç S.; AKARSU F.; Doğan Ö. H. (My University, 2023)
Quercus ilex (Holm oak) presents itself as trees up to 14–15 m tall in suitable growing site conditions and as shrubs in unsuitable areas. The purpose of this study was to determine the relationships between tree-ring widths of Q. ilex and vessel features, tree diameters, climate, and site conditions throughout Türkiye. A total of 1020 cores from 510 trees were collected from 102 sampled sites throughout Türkiye. After using standard dendroclimatology methods, all tree-ring analyses were performed on these chronologies. As a result, tree-ring boundaries were found to be less visible in Türkiye, like in other Mediterranean areas. Mean sensitivity ranged from 0.32 to 0.48 in different regions. Temperature during spring and summer months in the Mediterranean region has a negative effect on tree-ring widths in general. Winter temperature generally has a positive effect on tree-ring growth, and an increase in winter temperature may promote tree-ring width. Monthly total precipitation from November to July has a significant positive effect on tree-ring width and it is higher in the Aegean Region. While tree rings are wide in the trees found in lowlands, they are narrow in shrubs and at high elevations. There are clear negative relationships between tree-ring width and elevation, the amount of leaves in the litter, total litter amount, organic carbon, and soil pH. Regarding tree height, tree diameter, and vessel features, they have positive and high correlations with tree-ring width, except vessel frequency, which has a significant negative correlation. As a result of grouping, while the ratio of sites belonging to the dry group is low in regions that have trees with wide tree rings, the ratio of sites of the dry group is very high in İzmir and Datça, which have trees with narrow tree rings. The region with the widest rings is the Marmara Region, followed by the western Black Sea and the northern and southern Aegean, respectively. In conclusion, Q. ilex is a species that survives in both xeric and humid sites. It has adapted to dry conditions by forming narrow tree rings in Datça and continues to be found in tall bush-shrub forms with individuals over 140 years old. Specimens of the same age are in the form of trees with diameters of 50–60 cm and heights of 10–15 m in Ereğli. For these reasons, this species should be taken into consideration in afforestation and given priority in protection in its natural habitats where soil conditions are favorable, at a maximum distance of 23 km from the sea and in near-coastal areas.
Keywords: Tarımsal Bilimler; Ziraat; Ormancılık; Çevre Mühendisliği; Çevre Teknolojisi; Ekoloji ve Kirlenme; Gıda Mühendisliği; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Forestry; Environmental Engineering; Environmental Technology; Ecology and Pollution; Food Engineering; Engineering and Technology; Tarım ve Çevre Bilimleri (AGE); Bitki ve Hayvan Bilimleri; Tarım Bilimleri; Çevre / Ekoloji; ORMANCILIK; GIDA BİLİMİ VE TEKNOLOJİSİ; EKOLOJİ; Agriculture & Environment Sciences (AGE); PLANT & ANIMAL SCIENCE; AGRICULTURAL SCIENCES; ENVIRONMENT/ECOLOGY; FORESTRY; FOOD SCIENCE & TECHNOLOGY; ECOLOGY; Yaşam Bilimleri; Yemek bilimi; Ekoloji; Fizik Bilimleri; Life Sciences; Food Science; Ecology; Physical Sciences; elevation effect; growing site; Holm oak; regional differences; soil and tree rings; tree-ring growth